(untitled) (Journal Of Educational and Psychological Researches, 2022)
The study aimed to identify the degree of academic leaders practices at the University of Northern Border for creative leadership, which attribute to different variables (nature of work, employer, gender, years of experience in administrative work at the university). To achieve the goal of the study, the researcher used the descriptive approach survey. Therefore, the researcher used a questionnaire as a study tool, which consisted of (40) items that included dimensions (sensitivity to problems, initiative, originality, flexibility). The study sample consisted of (240) participants included (agents of colleges, and supporting deanships, and their employees) during the second semester of the academic year 1439/1440 AH. The results showed that the degree of creative leadership practice of the academic leaders came with a degree "sometimes" and with a general average of (3.31). On the other hand, the skills came as follows (flexibility, initiative, sensitivity to problems, originality). As indicated by results, there were statistically significant differences between the averages of the responses of the study sample due to the gender variable in the "initiative" dimension in favor of males. In light of the results, the researcher came out with several recommendations, most notably: • Establishing a flexible and effective system for communication between the academic leaders and their female agents and employees. • Encouraging academic leaders to make visits to their counterparts to adopt, to develop, and to innovate work methods that contribute to develop their creativity skills.